PERANCANGAN AVANT-GARDE FESYEN DENGAN PENGAPLIKASIAN DEKORATIF LIMBAH LOGAM TIMAH MENGGUNAKAN MELTING TECHNIQUE - Phang, Selena MarieAnn Heinrich; Gondoputranto, Olivia; Teowarang, Janet Rine (Universitas Ciputra Surabaya, 2025)
This research aims to warn and promote the dangers of heavy metal waste. Metals have different characteristics, some consist of very dangerous elements and some have less harmful effects yet still impacts the environment. The research results show that environmental pollution due to heavy metals is increasingly becoming an alarming problem and is of great concern throughout the world because of its negative impacts. By reprocessing tin metal waste from factories, with making use of melting technique, which later will form up shapes that will be the decorative elements in collection products with the style of Avant-garde and a part of Wearable Art. From the development of this design, it can help with the problem of metal waste and at the same time express artistic freedom through experimental work with sustainable materials. This research is a qualitative research that underlies constructivist beliefs. This research was conducted with 6 experts who are experts in different fields with different views, with 12 extreme users who have an interest in fashion. Experts and extreme users answered researcher’s questions using different and appropriate interview methods.